Motion Biomarkers Showing Maximum Contrast Between Healthy Subjects and Parkinson's Disease Patients Treated With Deep Brain Stimulation of the Subthalamic Nucleus. A Pilot Study - Kuhner, Andreas; Wiesmeier, Isabella Katharina; Cenciarini, Massimo; Maier, Timo Leon; Kammermeier, Stefan; Coenen, Volker Arnd; Burgard, Wolfram; Maurer, Christoph (Frontiers in Neuroscience, 2020)
BACKGROUND: Classic motion abnormalities in Parkinson’s disease (PD) such as tremor, bradykinesia, or rigidity, are well covered by standard clinical assessments such as the Unified Parkinson's Disease Rating Scale (UPDRS). However, PD includes motor abnormalities beyond the symptoms and signs as measured by UPDRS, such as the lack of anticipatory adjustments, or compromised movement smoothness which are difficult to assess clinically. Moreover, PD may entail motor abnormalities not yet known. All these abnormalities are quantifiable via motion capture, and may serve as biomarkers to diagnose and monitor PD. OBJECTIVE: In this pilot study we attempted to identify motion features revealing maximum contrast between healthy subjects and PD patients with deep brain stimulation (DBS) of the nucleus subthalamicus (STN) switched off and on as the first step to develop biomarkers for detecting and monitoring PD patients’ motor symptoms. METHODS: We performed 3D gait analysis in 7 out of 26 PD patients with DBS switched off and on, and in 25 healthy control subjects. We computed feature values for each stride, related to 22 body segments, 4 time derivatives, left-right mean vs. difference, and mean vs. variance across stride time. We then ranked the feature values according to their distinguishing power between PD patients and healthy subjects. RESULTS: The foot and lower leg segments proved better in classifying motor anomalies than any other segment. Higher degrees of time derivatives were superior to lower degrees (jerk > acceleration > velocity > displacement). The averaged movements across left and right demonstrated greater distinguishing power than left-right asymmetries. The variability of motion was superior to motion’s absolute values. CONCLUSIONS: This small pilot study identified the variability of a smoothness measure, ie jerk of the foot as the optimal signal to separate healthy subjects’ from PD patients’ gait. This biomarker is invisible to the clinicians’ naked eye, and is therefore not included in current motor assessments such as the UPDRS. We therefore recommend that more extensive investigations be conducted to identify the most powerful biomarkers to characterize motor abnormalities in PD. Future studies may challenge the composition of traditional assessments such as the UPDRS.